Knowledge, Awareness and Adherence to Antihypertensive Medication among Hypertensive Clients - DrMahadeo B Shinde, Bhakti Kulkarni (International Journal of Advanced Science and Technology, 2020)
Hypertension is a significant general wellbeing trouble and is part of an epidemiological change from transferable to noncommunicable sicknesses internationally. Hypertension is a treatable and preventable reason for mortality and dreariness malady. It is one of the significant general medical issues in both the developing and developed countries.study was undertaken to assess the patient’s knowledge, awareness and adherence to antihypertensive medication among hypertensive clients in a tertiary care centre. Methods-Descriptive cross-sectional Study was conducted. The study was undertaken outpatient departments  of tertiary care Krishna institute of medical sciences deemed to be university hospital .The patients attending medical outpatient departments and diagnosed as hypertension.  100 patients were selected through systematic randomized sampling method. Results-In current research study 60 % hypertensive male clients and  the majority 58% were from 60 and above age group however Only 41% clients know 140/90 mm of Hg called hypertension on other handonly 24% people know normal values of blood pressure 120/80mm of Hg. The majority was 79% for knowing smoking isrisk factor. Most 65% people aware about salty consumption leads tohypertension. The people are aware about 63% for high cholesterol dietis risk factor. Aging and family history of hypertension is risk factors known to client’s upto 44% and 50% respectively. The mean value of known risk factor is high cholesterol diet. The maximum awareness include thinking about having hypertension is 47%. Clients were less aware about realizing blood pressure values in diagnosis of hypertension were 23% and also this was mean value of awareness about hypertension. 27% clients were unaware of uncontrolled blood pressure can cause damage to organs.